Glatiramer acetate for treatment of relapsing–remitting multiple sclerosis. (April 2012) - Johnson, Kenneth P
Glatiramer acetate (GA; Copaxone ®, Teva Pharmaceuticals Inc.), approved in the USA in 1996 and EU in 2001 as first-line treatment for relapsing–remitting multiple sclerosis, is now available in 51 countries and recently gained approval for delaying conversion to clinically definite multiple sclerosis in patients with clinically isolated syndromes. Over the last 10–15 years, abundant research has better characterized the immunomodulatory activities and clinical efficacy and safety of GA. Relapsing–remitting multiple sclerosis patients taking GA continuously for up to 22 years as disease-modifying monotherapy experience minimal disability progression, and more than 1 million patient-years of experience attest to GA safety and tolerability. GA does not generate neutralizing antibodies, has no known drug interactions – making it a good candidate for combination therapy – and new formulations under evaluation may reduce injection frequency and injection-site reactions. The place of GA in the growing multiple sclerosis armamentarium will depend on its demonstrated benefit–risk ratio relative to that of newer investigational drugs.